An epidemic aggregate and individual-based model in a patchy environment - Phang, Piau; Ang, Kean Siang; Jane, Labadin (2013)
The spatial heterogeneity of susceptible-infected-recovered type of compartmental models are commonly expressed in ordinary differential equation based patchy models, in which all individuals are regarded as having the same type of epidemiological profile and demographic characteristics. However, these patchy aggregate models are often complicated to be constructed especially for three or more patches. Nevertheless, with the help of System Dynamics Modeler in NetLogo, we can conveniently construct a three-patch susceptible-infected-susceptible (SIS) model. A scenario analysis of three residential areas in which individuals are allowed to migrate among those areas was carried out. The same analysis was then carried out by an individual-based model simulated with agent-based modeling technique, in NetLogo as well. The simulation show that the results of individual-based model agree well with the aggregate model by carefully setting the parameters value involved. Hence, individual-based models could be potentially extended as a visualization tool for observing the evolution of epidemic dynamics taking into account weather conditions, landscape patterns and individual behaviours.